جهود الإمام يحي بن معين في فقه الحديث من خلال كتابه التاريخ والعلل - بالهادي ،سامية (University of Eloued جامعة الوادي, 2024)
"الحمد لله رب العالمين والصلاة والسلام على نبي الرحمة سيدنا محمد وعلى آله وأصحابه ومن تبعهم بإحسان إلى يوم الدين، وبعد: فتضمنت هذه الدراسة: أولاً: مبحثاً تمهيدياً قسمته إلى مطلبين الأول: تطرقت فيه إلى ترجمة الإمام يحي بن معين والمطلب الثاني: عرفت بكتابه التاريخ والعلل-رواية الدوري. ثانيا: المبحث الثاني كذلك قسمته إلى مطلبين: المطلب الأول: تناولت فيه مفهوم فقه الحديث وأهميته، والمطلب الثاني: قسمته إلى فروع. انتقيت فيه عدداً من العلوم التي تكلم عليها الإمام يحيى بن معين في فقه الحديث والمتمثلة في: علم الغريب وهذا أول ما بدأت به، ثم بعد ذلك ذكرت بعض الاختيارات الفقهية لهذا الإمام العظيم، وبينت في كل مسألة من وافقه ومن خالفه من أصحاب المذاهب الأربعة. ختمت هذا البحث بخاتمة ذكرت فيها أهم النتائج والتوصيات ووضحت أن أهمية فقه الحديث تبرز من خلال الإبحار والغوص في الحديث سنداً ومتناً وكذلك في الرد على شبهة أن عمل المحدثين ينحصر فقط في جمع الأحاديث في وعاء واحد. "Praise be to Allah, Lord of the worlds, and peace and blessings be upon the Prophet of mercy, our master Muhammad, and upon his family and companions, and those who follow them with kindness until the Day of Judgment. To proceed: This study included the following: First: A preliminary chapter divided into two sections. The first section discussed the biography of Imam Yahya ibn Ma'in, while the second section introduced his book History and causes- as narrated by Al-Duri. Second: The second chapter was also divided into two sections. The first section dealt with the concept of expertise in Hadith (jurisprudence of Hadith), and the second section outlined the rules of expertise in Hadith according to the Hadith scholars and its significance. In this chapter, I selected a number of issues addressed by Imam Yahya ibn Ma'in in the jurisprudence of Hadith, including: the science of *Gharib al-Hadith* (uncommon terms in Hadith), which was the first topic I discussed. I then moved on to the subject of ta'arudh (apparent contradictions) and explained how he reconciled between the Hadiths. I also covered issues related to creed and highlighted his beliefs in this regard. Then, I briefly mentioned his opinions on al-rijal (Hadith narrators), as his book is mainly concerned with this topic. Finally, I touched upon some of his juristic choices, explaining in each case who agreed with him and who differed from the scholars of the four major schools of thought. I concluded this research with a final chapter in which I outlined the most important findings and recommendations, clarifying that the significance of expertise in Hadith lies in the in-depth exploration and analysis of Hadiths in terms of both chain of transmission and content, as well as refuting the misconception that the work of Hadith scholars is merely the collection of Hadiths into a single compilation.
مذكرة ماسترتخصص علوم حديث
Keywords: يحيى بن معين; فقه الحديث; التاريخ والعلل; Yahya ibn Ma'in; expertise in Hadith; History and causes